Large-scale analogue quantum simulation using atom dot arrays - M. B. Donnelly; Y. Chung; R. Garreis; S. Plugge; D. Pye; M. Kiczynski; J. Támara-Isaza; M. M. Munia; S. Sutherland; B. Voisin; L. Kranz; Y. L. Hsueh; et al. (Nature, 2026)
Abstract In pursuit of a practical quantum advantage 1 , analogue quantum systems provide an invaluable way to simulate the physics of quantum materials 2–4 , quantum systems out of equilibrium 5,6 or interaction-induced localization 7 . Notable recent progress to realize such systems has been achieved in ultracold atoms 8–12 , superconducting circuits 13–15 and twisted van der Waals materials 16–19 . However, so far, these platforms have struggled to simulate large-scale strongly interacting fermionic systems at low temperatures, at which electronic correlations dominate materials properties and numerical simulations remain restricted in accuracy and scope 20,21 . Here we demonstrate the realization of a new platform consisting of large-scale 2D arrays of sub-nanometre precision-engineered atom-based quantum dots (15,000 sites) to simulate strongly interacting, low-temperature physics. By observing a metal–insulator (MI) transition on a 2D square lattice of atom-based quantum dots, we demonstrate independent and precise control of the on-site interaction U and tunnelling t . Magneto-transport measurements further indicate the formation of an insulating state driven by Mott–Hubbard/Anderson physics and promising signatures of correlated electron physics. These precision-engineered analogue quantum simulators provide a unique platform to simulate quantum materials on arbitrary 2D lattices and to explore many unanswered questions in the formation of quantum magnetism, interacting topological quantum matter and unconventional superconductivity.